Penerapan Terapi Afirmasi Positif pada Pasien dengan Harga Diri Rendah di Rumah Sakit Jiwa Palembang - Grace Septyanti; Novita Anggraini; Aprida Manurung (Jurnal Anestesi, 2024)
Low self-esteem is a persistent feeling of worthlessness and inferiority from negative self-evaluation of oneself. Complications for clients with low self-esteem include social isolation, hallucinations and violent behavior. The problem of low self-esteem requires appropriate intervention. One therapy that can be done by patients with low self-esteem is positive affirmation therapy. Positive affirmations are statements that strengthen positive beliefs within a person. This research aims to provide nursing care to mental patients with low self-esteem through positive affirmation therapy interventions at the Palembang mental hospital. The method used was a descriptive method with a nursing process approach on 3 patients with a One Group Pretest Posttest research design of positive affirmation therapy on patients with low self-esteem. The results of measurements via the Rosenberg Self Esteem Scale were obtained by the patient Mrs. Y with a score of 4 (low self-esteem) to 7 (high self-esteem), the score for Mrs. N with a score of 3 (low self-esteem) becomes 7 (high self-esteem) and Mrs. A with a score of 3 (low self-esteem) becomes 5 (low self-esteem). Conclusion: There is a decrease in the number of patients' self-esteem level scores through the Rosenberg Self-Esteem Scale measurement and a decrease in the number of symptoms that appear in patients with low self-esteem.